Clinical and psychological repercussions of videolaparoscopic tubal ligation: observational, single cohort, retrospective study - Dias, Daniel Spadoto; Dias, Rogério; Nahás-neto, Jorge; Nahás, Eliana Aguiar Petri; Leite, Nilton José; Bueloni-dias, Flávia Neves; Modotti, Waldir Pereira (Associação Paulista de Medicina - APM, 2014)
CONTEXT AND OBJECTIVE: Tubal ligation is one of the most commonly used contraceptive methods worldwide. Since the controversy over the potential effects of tubal sterilization still continues, this study aimed to evaluate the clinical and psychological repercussions of videolaparoscopic tubal ligation. DESIGN AND SETTING: Observational, single cohort, retrospective study, conducted in a tertiary public hospital. METHODS: A questionnaire was applied to 130 women aged 21-46 years who underwent videolaparoscopic tubal ligation by means of tubal ring insertion or bipolar electrocoagulation and sectioning, between January 1999 and December 2007. Menstrual cycle interval, intensity and duration of bleeding, premenstrual symptoms, dysmenorrhea, dyspareunia, noncyclic pelvic pain and degree of sexual satisfaction were assessed in this questionnaire. Each woman served as her own control, and comparisons were made between before and after the surgical procedure and between the two techniques used. RESULTS: The clinical and psychological repercussions were significant, with increases in bleeding (P = 0.001), premenstrual symptoms (P < 0.001), dysmenorrhea (P = 0.019) and noncyclic pelvic pain (P = 0.001); and reductions in the number of sexual intercourse occurrences per week (P = 0.001) and in libido (P = 0.001). Women aged ≤ 35 years at the time of sterilization were more likely to develop menstrual abnormalities. The bipolar electrocoagulation method showed greater clinical and psychological repercussions. CONCLUSION: Regardless of the technique used, videolaparoscopic tubal ligation had repercussions consisting of increased menstrual flow and premenstrual symptoms, especially in women aged ≤ 35 years, and also had a negative influence on sexual activity.

CONTEXTO E OBJETIVO: A ligadura tubária é um dos métodos contraceptivos mais utilizados em todo o mundo. Como a controvérsia sobre seus possíveis efeitos ainda continua, o objetivo deste estudo foi avaliar as repercussões clínicas e psíquicas da laqueadura videolaparoscópica. TIPO DE ESTUDO E LOCAL: Estudo observacional de coorte único, retrospectivo, conduzido em hospital público terciário. MÉTODOS: Foi aplicado um questionário a 130 mulheres, entre 21-46 anos, submetidas à ligadura tubária videolaparoscópica, pelas técnicas de eletrocoagulação bipolar/secção ou inserção do anel tubário, entre janeiro de 1999 e dezembro de 2007. Nesse questionário avaliou-se: intervalo do ciclo menstrual, intensidade e duração do sangramento, sintomas pré-menstruais, dismenorreia, dispareunia, dor pélvica não cíclica e grau de satisfação sexual. Cada mulher serviu como seu próprio controle, foi realizada análise comparativa entre os períodos pré- e pós-cirúrgico e entre as duas técnicas utilizadas. RESULTADOS: As repercussões clínicas e psicológicas mostraram-se significativas, com aumento de sangramento (P = 0,001), de sintomas pré-menstruais (P < 0,001), dismenorreia (P = 0,019), dor pélvica não cíclica (P = 0,001), e redução no número de relações sexuais por semana (P = 0,001) e na libido (P = 0,001). Mulheres com idade ≤ 35 anos, no momento da laqueadura, mostraram-se mais propensas a desenvolverem alterações menstruais. A técnica de eletrocoagulação bipolar mostrou maiores repercussões clínicas e psíquicas. CONCLUSÃO: A ligadura tubária videolaparoscópica, independentemente da técnica, repercutiu com aumento do fluxo menstrual e de sintomas pré-menstruais, principalmente em mulheres com idade ≤ 35 anos, tendo também influenciado negativamente na atividade sexual.
Repercussões clínicas e psíquicas da ligadura tubária videolaparoscópica: estudo observacional de coorte única, retrospectivo
Keywords: Serviços de planejamento familiar; Laparoscopia; Distúrbios menstruais; Esterilização reprodutiva; Esterilização tubária; Family planning services; Laparoscopy; Menstruation disturbances; Sterilization, reproductive; Sterilization, tubal